2000
DOI: 10.1046/j.1365-2141.2000.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation management in primary care: a trial-based economic evaluation

Abstract: The demand for anticoagulation management is increasing because of a widening of the indications of treatment. A primary care clinic using near-patient testing and computer decision support software is one model of care to meet this increased demand. The study aimed to determine the cost and cost-effectiveness of primary care-based anticoagulation management in comparison with 'traditional' hospital care-based provision by means of a cost-effectiveness analysis using data from a Birmingham-based multicentre ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 5 publications
1
29
0
1
Order By: Relevance
“…This contrasts with the results of a Belgian study which found the use of a PoCT device for anticoagulant management combined with a multifaceted education intervention was dominant to usual care in GP [19]. Anticoagulant management in GP using PoCT, was also found to be more costly by Parry et al [22]. This UK study investigated the cost-effectiveness of PoCT, using data obtained through an RCT of PoCT and computerised decision support to manage anticoagulation therapy in GP.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This contrasts with the results of a Belgian study which found the use of a PoCT device for anticoagulant management combined with a multifaceted education intervention was dominant to usual care in GP [19]. Anticoagulant management in GP using PoCT, was also found to be more costly by Parry et al [22]. This UK study investigated the cost-effectiveness of PoCT, using data obtained through an RCT of PoCT and computerised decision support to manage anticoagulation therapy in GP.…”
Section: Discussionmentioning
confidence: 90%
“…Comparing the results of the cost and the cost-effectiveness analyses for this Trial with other studies is difficult because of the limited research in this area [16-22]. Those studies that do exist are also limited in their scope and design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies conducted in specialist hospital clinics (8 studies) showed INR monitoring costs that ranged from $11.75 for drawing blood and measurement of prothrombin time (Menzin et al. , 1995) to $45.57 for a new‐patient appointment (Parry, Fitzmaurice & Raftery, 2000). For studies conducted in general practice (4 studies), the range of costs was $24.19 for a GP taking a blood sample with hospital analysis and dosing (Jowett et al.…”
Section: Resultsmentioning
confidence: 99%
“…Data are conflicting on potential cost benefits; however, the most recent UK data suggest no cost saving with community monitoring, except in domiciliary patients (Fitzmaurice, Hobbs & Murray, 1998; Lafata et al. , 2000; Parry, Fitzmaurice & Raftery, 2000). POC testing devices may also give selected patients the opportunity for self‐testing and self‐management.…”
Section: Introductionmentioning
confidence: 99%